A new species of Parasyrisca (Araneae: Gnaphosidae) from Xinjiang, China - Marusik, Yuri M.; Fritzén, Niclas R. (Zootaxa, 2009)
The Holarctic genus Parasyrisca Schenkel, 1963 so far encompasses 46 species (Platnick 2008). It is one of the best-known species-diverse gnaphosid genera in the northern Hemisphere, due to a recent revision (Ovtsharenko et al. 1995). Most of the species are known from the Caucasus, Central Asia, South Siberia and Mongolia. While studying spiders of Central Xinjiang we found one undescribed Parasyrisca species (Marusik et al. 2007). Here we present a description of it. The format of the description and standard abbreviations of morphological terms follow those of Platnick & Shadab (1975) and Ovtsharenko et al. (1995). Specimens were photographed using an Olympus SZX12 stereomicroscope and Olympus Camedia C-5050 camera in the Zoological Museum, University of Turku. The images have been composed using “CombineZM” image stacking software. All measurements are given in millimeters. Types will be deposited in the Zoological Institute in Beijing (ZIB).